Improving wear resistance of 304 stainless steel reinforced AA7075 aluminum matrix composite by micro-arc oxidation - Gecu, Ridvan; Yurekturk, Yakup; Tekoglu, Emre; Muhaffel, Faiz; Karaaslan, Ahmet (ELSEVIER SCIENCE SA, 2019)
The present study aimed to enhance wear resistance of 304 stainless steel (SS) reinforced AA7075 aluminum matrix bimetal composite by micro-arc oxidation (MAO) process. Monolithic AA7075 alloy and 304 SS reinforced AA7075 matrix composites with and without MAO coating were subjected to ball-on-disc type tribometer with testing loads of 1, 5, 10 and 15 N. Continuous interfacial reaction layer consisted of theta-Fe4Al13 and eta-Fe2Al5 phases was obtained at 304 SS/AA7075 interface. These phases contributed to improvement of the wear resistance of bimetal composite by reducing adhesive wear considerably. With the application of MAO treatment, wear-resistant Al2O3 (alumina) layer was formed on the surface of composite. MAO coating provided better wear resistance as compared to the original state of the composite, especially at higher loads during wear tests.
Keywords: Bimetal composite; Melt infiltration casting; Micro-arc oxidation; Alumina; Wear; DRY SLIDING WEAR; MECHANICAL-PROPERTIES; ALLOY; BEHAVIOR; AL2O3; Materials Science; Physics